On the nonexistence of a law of the iterated logarithm for weighted sums of identically distributed random variables. (1990) - Adler, André
Abstract : For weighted sums of independent and identically distributed random variables, conditions are placed under which a generalized law of the iterated logarithm cannot hold, thereby extending the usual nonweighted situation.